2018
DOI: 10.1002/ctpp.201700171
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the primary processes that lead to the drop in divertor target ion current at detachment in TCV

Abstract: Using SOLPS‐ITER, we model a TCV conventional divertor discharge density ramp to understand the role of various processes in the loss of target ion current. We find that recombination is not a strong contributor to the rollover of the target ion current at detachment. In contrast, the divertor ion source appears to play a central role in magnitude (the source of most of the ion target current) and time, apparently dropping during the density ramps as a result of a drop in power available for ionization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
77
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(99 citation statements)
references
References 11 publications
20
77
1
Order By: Relevance
“…This makes sense because target T e 1.2eV at this higher upstream density, whereas at target flux rollover target T e 3.2eV. This is in contrast to some previous results [33] in which flux rollover occurred at lower temperatures, but in agreement with recent experiments [34,18] and simulations [35] of TCV. There are several ways in which target flux can be reduced, recombination being one of them, so discrepancies may be seen between studies in different regimes.…”
Section: The Role Of Particle and Energy Losssupporting
confidence: 85%
“…This makes sense because target T e 1.2eV at this higher upstream density, whereas at target flux rollover target T e 3.2eV. This is in contrast to some previous results [33] in which flux rollover occurred at lower temperatures, but in agreement with recent experiments [34,18] and simulations [35] of TCV. There are several ways in which target flux can be reduced, recombination being one of them, so discrepancies may be seen between studies in different regimes.…”
Section: The Role Of Particle and Energy Losssupporting
confidence: 85%
“…The mechanism is explained as follows: (a) the polarization electric field E p is produced as a result of the charge separation of ions and electrons by the curvature drifts (see the potential profile in Figure 2e); (b) then, the resultant E p × B drift of ions and electrons takes place in the same direction; and (c) next, the blob shape starts deforming into a mushroom shape as seen from Figure 2b and c. This may be mainly due to the Kelvin-Helmholtz instability. [22] These properties of the plasma blob are in agreement with those from other studies. [19][20][21] It should be noted that a pair of low-density and high-density region of impurity test particles has been left in the region where the blob has been formed.…”
Section: Resultssupporting
confidence: 91%
“…Hence, this mechanism is not the one setting the density SOL width, which in turn limits the power SOL width as proposed by the model proposed by Goldston. [17] In consequence, it seems to point out that it is not the mechanism responsible for the q narrow feature as suggested by Kočan et al [18] In Figure 3a, the value of each temporal and toroidal point is reported as small scatter, which also permits us to remark that the heat flux profile in the SOL is highly intermittent. In particular, the maximum value of the heat flux is about 3 times the mean values at the separatrix, but this ratio goes up to more than 5 in the far SOL, thus the temporal variation of heat flux is not to be neglected.…”
Section: Power Sol Width and Narrow Feature In Anisothermal Simulationsmentioning
confidence: 50%